Pengembangan Media Pembelajaran Berbasis Video Tenun di Desa Sukarara untuk Meningkatkan Motivasi Belajar IPA pada Materi Gaya Gesek - Martiana, Rina; Hadiprayitno, Gito (Yayasan Arfah Bin Haji Muhammad Saleh, 2025)
Education in the 21st century has undergone a significant paradigm transformation, requiring learning to be less one-way and more student-centred. The integration of technology in education is becoming increasingly important, given the need to develop 21st century competencies such as communication, collaboration, critical thinking and creativity. In this context, science learning should be designed to be relevant and meaningful to students, by connecting scientific concepts with everyday life. This research aims to develop video-based learning media about weaving in Sukarara Village, with a focus on frictional force material in Science learning. The method used is the DDDE model, which includes the Decide, Design, Develop, and Evaluate stages. The development results in the form of animated videos and quiz games have been validated by science teachers and media expert lecturers. The validation results show that the video has high feasibility with an average score of 91% from the teacher and 83% from the lecturer. This learning media succeeded in increasing student motivation by linking scientific concepts with local wisdom and real practices in the village. Nevertheless, challenges in understanding the material still exist, so further guidance is recommended. This study concludes that the development of video-based media is effective in increasing the motivation to learn science and the relevance of the material to students' daily lives.